Histopathological Findings of Acute Kidney Injury in Pediatric Coronavirus Disease-19 Patients: A Systematic Review - Muhammad Tidar Abiyu Amiruddin, -
Abstract Introduction: Acute kidney injury (AKI) is a complication of coronavirus disease-19 (COVID-19), and the pathophysiology of AKI in COVID-19 could be determined as multifactorial. The exact prevalence of AKI in COVID-19 patients is growing over time. Due to the difficulties, kidney biopsy is performed in a small minority of AKI patients infected with COVID-19.